Paraspinal myositis in a patient with COVID-19 infection: a case report - Watsachon Pangkanon; Natnicha Leelaviwat; Sakditad Saowapa; En-Dien Liao; J. Drew Payne (SpringerOpen, 2023)
Abstract Myalgia is one of the most common symptoms of COVID-19 infection. With the progression of the COVID-19 pandemic, emerging cases of COVID-related myositis have been reported. However, COVID-19-related myositis of the paraspinal muscle is uncommon. We present a 66-year-old female who was admitted to the hospital for hemorrhagic shock secondary to gastrointestinal bleeding. She developed COVID-19 respiratory tract infection symptoms on the second day of admission with reported severe lower back pain 3 days later. Serum creatinine kinase level was slightly elevated, and magnetic resonance imaging (MRI) revealed paraspinal myositis.